Limitations of serodiagnosis in chlamydial genital tract infections. - Ngeow, Y.F. (1996)
Infection with Chlamydia trachomatis results in the formation of a variety of antibodies with group, species, subspecies and serovarspecificity. Sera from patients with genital tract infections often show broad reactivity in serological tests. This may be due to the presence of cross-reacting antibodies, repeated infections by different serotypes or concurrent genital and respiratory infections by different chlamydial species. Other factors contributing to difficulties in interpretation include how antibody titres in acute mucosal infections, the occurrence of latent infections and reactivations, and the persistence of IgG which does not allow the differentiation of past from current infections. For these reasons, serology alone is inadequate for the diagnosis of uncomplicated lower genital tract infections. In upper genital tract infections, however, because of difficulties with sampling from the infected site, a positive serology may be the only indications of chlamydial involvement. This paper discusses the principles of chlamydial antibody assays, difficulties with their interpretation and their role in the diagnosis of upper and lower genital tract infections.